The necessary unity of opposites : the dialectical thinking of Northrop Frye - Graham, Brian Russell (Frye studies., 2011)
Graham contends that it was the method of Frye's thinking - his dialectic ability to see opposing concepts as a unity rather than a dichotomy - that allowed him to transcend binary constructs and formulate new conclusions and questions about literature, politics, and society.